Thermal Ablation of Metastatic Colon Cancer to the Liver - Camacho, Juan C.; Petre, Elena N.; Sofocleous, Constantinos T. (Seminars in Interventional Radiology, 2019)
Colorectal cancer (CRC) is responsible for approximately 10% of cancer-related deaths in the Western world. Liver metastases are frequently seen at the time of diagnosis and throughout the course of the disease. Surgical resection is often considered as it provides long-term survival; however, few patients are candidates for resection. Percutaneous ablative therapies are also used in the management of this patient population. Different thermal ablation (TA) technologies are available including radiofrequency ablation, microwave ablation (MWA), laser, and cryoablation. There is growing evidence about the role of interventional oncology and image-guided percutaneous ablation in the management of metastatic colorectal liver disease. This article aims to outline the technical considerations, outcomes, and rational of TA in the management of patients with CRC liver metastases, focusing on the emerging role of MWA.
Keywords: metastatic colon cancer; liver metastasis; thermal ablation; survival